Will You Continue to Use Food Delivery Services During the Transition to the Endemic Phase of the Covid-19 Pandemic? - Sin, Liem Gai; Goh, Wei Zheng; Goh, Chin Chuan; Kumaresan, Haarshenni A/P; Goh, Pei Kai (AIBPM Publisher, 2022)
Malaysia entered the transition to endemic phase of the Covid-19 pandemic on April 1, 2022. After two years of fighting the pandemic, the transition to the endemic phase is an exit strategy that enables Malaysians to return to a nearly normal life. This paper examines whether customers will continue to use food delivery services now that most individuals are permitted to return to work physically. This study will also examine if perceived usefulness, ease of use, enjoyment, trust, social influence, and attitude impact customer behavioral intention toward food delivery services and whether attitude mediates the aforementioned relationship. 200 Malaysians participated in the survey. The findings indicate that perceived usefulness, ease of use, enjoyment, trust, social influence, and attitude influence consumers' behavioral intentions for meal delivery services. The link between perceived usefulness, ease of use, enjoyment, trust, social influence, and behavioral intention is mediated by attitude. Recommendations and consequences were presented.Â Keywords: Perceived usefulness, Ease of use, Enjoyment, Trust, Social influence, Attitude, Behavioral Intention, Malaysia.